0.3x-2.3=2.4x+1.8

Simple and best practice solution for 0.3x-2.3=2.4x+1.8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.3x-2.3=2.4x+1.8 equation:


Simplifying
0.3x + -2.3 = 2.4x + 1.8

Reorder the terms:
-2.3 + 0.3x = 2.4x + 1.8

Reorder the terms:
-2.3 + 0.3x = 1.8 + 2.4x

Solving
-2.3 + 0.3x = 1.8 + 2.4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2.4x' to each side of the equation.
-2.3 + 0.3x + -2.4x = 1.8 + 2.4x + -2.4x

Combine like terms: 0.3x + -2.4x = -2.1x
-2.3 + -2.1x = 1.8 + 2.4x + -2.4x

Combine like terms: 2.4x + -2.4x = 0.0
-2.3 + -2.1x = 1.8 + 0.0
-2.3 + -2.1x = 1.8

Add '2.3' to each side of the equation.
-2.3 + 2.3 + -2.1x = 1.8 + 2.3

Combine like terms: -2.3 + 2.3 = 0.0
0.0 + -2.1x = 1.8 + 2.3
-2.1x = 1.8 + 2.3

Combine like terms: 1.8 + 2.3 = 4.1
-2.1x = 4.1

Divide each side by '-2.1'.
x = -1.952380952

Simplifying
x = -1.952380952

See similar equations:

| 4.6+(-5.9)= | | 4x-2(x+7)=-46 | | -1(x+2)-2x=-2(x+q) | | 4x-2(x+7)=-45 | | -5x-125=44+8x | | 17=-5(3x-7)+6(-8+5x) | | -8.5h-7.5-9.5=-15.5 | | 2x+5y-9=0 | | 6x-9=3x+11 | | y-6=-2(x+2) | | (X-10)-4=12 | | 1.1y-(y-0.6)+0.3=0 | | 3x+3(x+5)=30 | | 3-5(4x+5)=78 | | 4(-3+1)=-10(x-4)-14 | | 4x^2-98+180=0 | | 4-7(1-2r)=15.5 | | -29-x=-7x+67 | | 7(x-3)=-3x+89 | | -7+3x-2x=17 | | 5y^5=20 | | 3500+1680x=175000+550x | | 8(3n-8)=8 | | 5.9-p=2 | | x-153=55+9x | | 6.3=7.0x | | -4.5(7x-6.5)=-23.5 | | 52-4x=10-10x | | 3x-2(x-3)+4(x+1)=-5 | | 2x-102-10x=42 | | -9(5-5.5k)=26.5 | | 14-8m= |

Equations solver categories